Methods of machine learning in modern metrology - Aschepkov, Valeriy (Видавництво Львівської політехніки, 2024)
In the modern world of scientific and technological progress, the requirements for the accuracy and reliability of measurements are becoming increasingly stringent. The rapid development of machine learning (ML) methods opens up perspectives for improving metrological processes and enhancing the quality of measurements. This article explores the potential application of ML methods in metrology, outlining the main types of ML models in automatic instrument calibration, analysis, and prediction of data. Attention is paid to the development of hybrid approaches that combine ML methods with traditional metrological methods for the optimal solution of complex measurement tasks.
Keywords: machine learning; metrology; measurement accuracy; instrument calibration; data analysis; forecasting